Political Economy of Economic Policy - The Monetary Reconstruction Program (Serbia 1994) as a Case Study - Madžar, Ljubomir (Panoeconomicus, 2022)
The paper deals with initiation and destiny of the unique 1994 Program of combating the extreme Serbian hyperinflation. Despite the originality of the Program and decisiveness with which the related steps had been undertaken, the Program lasted not much more than half a year. It turned out to be unsustainable as it is collided with inefficient institutional framework where contracts and rule of law were not honored, and employees, in self-managed firms, decided on their own remuneration. We show that for lasting stabilization a far-reaching institutional reform was needed, and for implementing such reform an equally radical reform of the political system was necessary. However, there was not political will for these reforms, since they would oust the then political and economic elite from the power. Keywords: Hyperinflation, Stabilization, Currency board, Credibility, Institutional deficiencies, Political constraints, Institutionally conditioned unsustainability. JEL: E31, E63, E65.